Gamification Strategies: a web system to disseminate production information to construction workers (Research, Society and Development, 2021)
The construction industry has sought to modernize itself to keep up with the technological changes that have been taking place in people's daily lives, but the lack of transparency in the construction process leads to difficulties in understanding by workers and communication problems between the tactical and operational levels. This article aims to propose a solution to facilitate communication between workers and managers at the construction site to improve the understanding of work goals. This is exploratory research with a Design Science methodological approach using the Design Science Research method. The research is divided into three phases, namely: (1) Understanding, (2) Development and (3) Assessments. The article corresponds to the solution development phase. Involving analysis of requirements of managers and construction workers to develop a web system with a gamified interface. From the information produced and the literature review, a gamified system was developed. Most workers have a huge lack of recognition and have a low level of education, which justifies the inclusion of gamified strategies to improve communication. The results show that the proposed solution can minimize this problem.